Lady Gaga - hiperrzeczywisty buntownik na sprzedaż jako propozycja tożsamościowa dla globalnej młodzieży - Wierzba, Paulina (Wydawnictwo DiG, 2013)
The article analyzes the phenomenon of Lady Gaga, one of the biggest modern culture icons. It shows the influence of the figure on the identity of global youth being constructed. Her image, videos, rhythm and song lyrics describe and express life experience of global teenagers, socializing them to their function in modern reality. The author tries to prove that in contemporary reality even a rebellion has become a product to sell. Youth idols who have undergone the way from counter-culture to pop culture occur to be part of the mainstream. Lady Gaga is more a theory than a theory itself. She constitutes the lens which concentrate the theoretical contexts of transformations of young generation identity, bothering many researchers of postmodern culture.
Keywords: kultura popularna; kultura masowa; tożsamość; młodzież